Πόντιση ΦΡ νέου τύπου στον δίαυλο Αλεξανδρούπολης (Hellenic Navy, 2017)
: Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Μουσική Υπότιτλοι AUTHORWAVE Μουσική Υπότιτλοι AUTHORWAVE Μουσική Υπότιτλοι AUTHORWAVE Μουσική Υπότιτλοι AUTHORWAVE Μουσική Υπότιτλοι AUTHORWAVE Μουσική Υπότιτλοι AUTHORWAVE Μουσική Υπότιτλοι AUTHORWAVE Μουσική Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE